Awareness of Stress-Reduction Interventions on Work Attitudes: The Impact of Tenure and Staff Group in Australian Universities - Pignata, Silvia; Winefield, Anthony H.; Provis, Chris; Boyd, Carolyn M. (Frontiers in Psychology, 2016)
This study explored the impact of staff group role and length of organizational tenure in the relationship between the awareness of stress interventions (termed intervention awareness: IA) and the work-related attitudinal outcomes of university employees. A two-wave longitudinal study of a sample of 869 employees from 13 universities completed a psychosocial work factors and health questionnaire. Hierarchical regression analyses examined the contribution of staff role and different lengths of organizational tenure with IA and employees’ reports of job satisfaction, affective organizational commitment, trust in senior management, and perceived procedural justice. Employees' length of tenure affected the relation between IA and work attitudes, and there were also differences between academic and non-academic staff groups. For non-academic employees, IA predicted job satisfaction, affective organizational commitment, trust in senior management, and perceived procedural justice. However, for academics, IA only predicted job satisfaction and trust which identifies a need to increase the visibility of organizational interventions. Across the tenure groups, IA predicted: (1) perceived procedural justice for employees with five or less years of tenure; (2) job satisfaction for employees with 0–19 years of tenure; (3) trust in senior management for employees with 6–19 years of tenure; and (4) affective organizational commitment for employees with a tenure length of 6–10 years. Employees working at the university for an intermediate period had the most positive perceptions of their organization in terms of IA, job satisfaction, trust in senior management, and affective organizational commitment, whereas employees with 20–38 years of tenure had the least positive perceptions. Results suggest that employees in the middle of their careers report the most positive perceptions of their university. The findings highlight the need to attend to contextual issues in organizational stress and wellbeing interventions and suggest that management may need to implement new strategies and/or promote existing stress-management and reduction strategies to academics, and employees whom are either new to the university or those who have been working for the organization for longer periods of time to ensure that they are aware of organizational strategies to promote employee wellbeing and morale within their work environments.